PENERAPAN TEKNIK FUSION PADA SCONES BARUASA BERBASIS TEPUNG LOKAL - St. Hadijah; Riska Veronika; Dewi Andriani (HOME : Hospitality and Gastronomy Research Journal, 2026)
This study aimed to develop a fusion pastry product known as Scones Baruasa, which combines scones as a Western quick bread with the traditional Bugis Makassar cake baruasa through partial substitution of wheat flour using sorghum and banana flour. An experimental method was applied in two stages, including local flour substitution formulation and fusion technique implementation based on the sensory characteristics of baruasa. Sensory evaluation was conducted in stages involving 25 semi trained panelists, 3 expert panelists, and 200 consumer panelists using a seven point hedonic scale. The results indicated that the optimal formulation was achieved with 15 percent sorghum flour and 10 percent banana flour substitution. Scones Baruasa obtained an overall acceptance score of 5.34, categorized as liked. Although the acceptance level was lower than that of conventional scones, the product demonstrated strong local sensory characteristics, particularly in aroma and flavor. Scones Baruasa has potential to be developed as a fusion pastry product based on local culture and sustainable gastronomy.